Base-Promoted 1,6-Aza-Michael Addition of Azauracils to para-Quinone Methides - Dash, Rupashri; Hota, Sudhir Kumar; Murarka, Sandip (Synthesis, 2023)
We report an efficient higher order conjugate addition of azauracils to substituted para-quinone methides (p-QMs) mediated by triethylamine to furnish hitherto unknown diarylmethane scaffolds through construction of a C–N bond. The protocol features mild conditions, high atom economy, and broad scope, and enables convenient access to biologically relevant new chemical entities (NCEs) comprised of p-QM and azauracil hybrids in good to excellent yields.
Keywords: azauracil; para-quinone methides; 1,6-addition; aza-Michael; metal-free